Reviewing Criminal Threats Against Falsification of Covid-19 Certificate by Medical Personnel - Nuzul Quraniati Rohmah (PT. Anagata Sembagi Education, 2024)
This article discusses the relationship between law and society, beginning with a review of the statement “where there is society, there is law” (ubi societas ibi ius). The research highlights how societies form laws in an effort to protect themselves or their groups. However, societal developments are often faster than legal reforms, resulting in some regulations becoming irrelevant to the current situation. The Covid-19 pandemic, for example, has changed various aspects of people's lives, including travel restrictions and requirements. Documents such as the Covid-19 Certificate have become important in a pandemic situation, but cases of forgery have also increased. Syndicates of Covid-19 Certificate forgery, including perpetrators who are medical personnel, indicate a serious violation of the law. The imposition of criminal and administrative sanctions is necessary to uphold justice and emphasize the importance of complying with the code of ethics, especially in the context of health services. Through an understanding of applicable regulations and laws, as well as fair enforcement of sanctions, it is hoped that the community can obtain justice and protection in accordance with current social and health conditions.